2019
DOI: 10.1002/advs.201900264
|View full text |Cite
|
Sign up to set email alerts
|

Pulverization‐Tolerance and Capacity Recovery of Copper Sulfide for High‐Performance Sodium Storage

Abstract: Finding suitable electrode materials is one of the challenges for the commercialization of a sodium ion battery due to its pulverization accompanied by high volume expansion upon sodiation. Here, copper sulfide is suggested as a superior electrode material with high capacity, high rate, and long‐term cyclability owing to its unique conversion reaction mechanism that is pulverization‐tolerant and thus induces the capacity recovery. Such a desirable consequence comes from the combined effect among formation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 35 publications
3
28
0
3
Order By: Relevance
“…Figure 12j, m show the ex-situ SAED patterns of the full discharge and charge products. The results of ex-situ SAED patterns are [116] in accordance with the result of ex-situ XRD, confirming the discharge products are Na 2 S and Co and the charge product is Co 9 S 8 . Analysis of ex-situ XRD and SAED indicates a highly reversible conversion mechanism for the Co 9 S 8 during sodiation/desodiation.…”
Section: Sodium Storage Mechanism Investigated By In-situ and Ex-situsupporting
confidence: 74%
See 1 more Smart Citation
“…Figure 12j, m show the ex-situ SAED patterns of the full discharge and charge products. The results of ex-situ SAED patterns are [116] in accordance with the result of ex-situ XRD, confirming the discharge products are Na 2 S and Co and the charge product is Co 9 S 8 . Analysis of ex-situ XRD and SAED indicates a highly reversible conversion mechanism for the Co 9 S 8 during sodiation/desodiation.…”
Section: Sodium Storage Mechanism Investigated By In-situ and Ex-situsupporting
confidence: 74%
“…On the other hand, Yuk et al revealed another sodiation mechanism of copper sulfide by ex-situ TEM and ex-situ HRTEM [116]. Figure 11i shows the structural evolution of CuS nanoplates upon charge/discharge.…”
Section: Sodium Storage Mechanism Investigated By In-situ and Ex-situmentioning
confidence: 99%
“…Based on the above results, the Na + -storage performance of the Cu 1.81 S MTs is superior to that of most of the previously reported Cu x S electrodes, 17,21,48,49,51,52 which can be ascribed to the fact that its unique triangular support structures accommodate volume changes during sodiation/desodiation, which effectively suppresses the pulverization of active materials ( Figure 5B). In addition, the hollow truss structure ensures the electrolyte rapid infiltration and shortens the diffusion length of electron/Na + ions for the acceleration of electrochemical kinetics as disclosed by electrochemical impedance spectroscopy (EIS) spectra (see Table S1 for details).…”
Section: Resultsmentioning
confidence: 60%
“…The electrode delivers an initial discharge/charge capacity of 563/487 mAh g À1 , corresponding to an initial Coulombic efficiency (CE) of 86.5%. The initial capacity loss of the MT electrode is much smaller than that of other Cu x S electrodes, 17,21,48,49,51,52 which may be due to the formation of a more stable solid electrolyte interphase film. Compared with the Cu x S HMCs, the Cu 1.81 S MTs illustrate a significant stability of 200 cycles at 0.1 A g À1 ( Figure 4C).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation